Resilience and Parenting Stress in Mothers who have Children with Mental Retardation during the COVID-19 Pandemic - Indriasari, Fika Nur (Fakultas Ilmu-ilmu Kesehatan, 2022)
The mental health of parents who have children with special needs at the time of the covid-19 pandemic needs attention. Social restrictions that must be done trigger increased stress parenting in mothers who have children with mental retardation. Children become vulnerable to violent behavior from the surrounding environment as a result of lack of parental knowledge in understanding their child's growth and development. Mothers have more roles, not only as caregivers but also as therapists and educators who replace teachers in schools. The level of maternal resilience affects how good coping management so that it can overcome the stressors experienced. The purpose of this study was to find out the effects of resilience and stress parenting experienced by mothers who have children with mental retardation during the covid-19 pandemic. The research design used is cross sectional. The population in this study was a mother who had a child of mental retardation and attended special school Pembina Yogyakarta, Indonesia. The sampling technique used is purposive sampling. The results showed that the value of p value 0.001 < 0.05 which means there is an influence on resilience levels with parenting stress experienced by mothers who have children mentally retarded during the covid-19 pandemic. Maternal stress parenting levels fall into the low category but maternal resilience is in the moderate category